Adenine, a key player in biology and medicinal chemistry - Fillion, Alexandra; Vichier-Guerre, Sophie; Arimondo, Paola Barbara (Comptes Rendus. Chimie)
Adenine is one of the most ubiquitous heterocycles in life. In addition of being one of the four nucleobases constituting DNA and RNA, adenine is also contained in many biological molecules (ATP, SAM, NAD, cAMP, coA ...) that have fundamental roles in the functioning of living systems, e.g. energy source, cofactors of enzymes and proteins. As such, the adenine has naturally become a privileged scaffold explored in medicinal chemistry for biomedical applications. Many chemical modifications and Structure-Activity Relationships studies have been carried out on the adenine scaffold to result in potent analogues with various biological activities. Today, numerous adenine-based inhibitors are used to treat a wide range of diseases including cancer, viral and bacterial diseases. This review aims to introduce the adenine and discuss adenine-based inhibitors, their design and use for different therapeutic targets through examples of drugs and compounds that reached clinical and preclinical trials.